2017
DOI: 10.3892/mmr.2017.7076
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-613 inhibits proliferation and invasion of renal cell carcinoma cells through targeting FZD7

Abstract: MicroRNAs (miRNAs) have emerged as critical regulators in cancer progression. miR‑613 has been reported as a tumor suppressor gene in many types of human cancers. However, the function of miR‑613 in renal cell carcinoma (RCC) remains unclear. In the present study, the authors aimed to detect the expression of miR‑613 and its function in RCC cell lines. miR‑613 was reported to be significantly downregulated RCC cell lines. Functional analyses demonstrated that overexpression of miR‑613 significantly decreased R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“… 14 miR-613 has been demonstrated to be downregulated in several types of cancers including renal cell carcinoma, glioma, breast cancer, and cervical cancer, implying that miR-613 may act as a tumor suppressor gene. 15 - 18 However, its function and mechanism in PC remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“… 14 miR-613 has been demonstrated to be downregulated in several types of cancers including renal cell carcinoma, glioma, breast cancer, and cervical cancer, implying that miR-613 may act as a tumor suppressor gene. 15 - 18 However, its function and mechanism in PC remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…10 miR-613 has been demonstrated to be downregulated in several types of cancers including renal cell carcinoma, glioma, lung cancer, and cervical cancer, implying that miR-613 may act as a tumor suppressor gene. [11][12][13][14] For instance, miR-613 targeted CDK9 to inhibit proliferation and invasion. 15 It was also reported that downregulation of miR-613 facilitated liver cancer stem cells, indicating that miR-613 was involved in tumor stemness.…”
Section: Introductionmentioning
confidence: 99%
“…Almost all members of the Wnt receptor family, such as FZD4, 6, 7, 8, and 10 have been reported to be regulated by different miRNAs in multiple cancer types including colorectal cancer, prostate cancer, breast cancer (Gong et al, 2014;Kim B.-K. et al, 2015;Jiang et al, 2016;Song et al, 2017;Li Z.-T. et al, 2020). In a few cases, upregulation of miRNAs regulating the negative (Kim et al, 2011;Hata et al, 2017;Poodineh et al, 2020).…”
Section: Receptorsmentioning
confidence: 99%